2006
DOI: 10.1002/ajmg.b.30338
|View full text |Cite
|
Sign up to set email alerts
|

BDNF gene variants and brain morphology in schizophrenia

Abstract: The objective was to investigate putative associations between brain-derived neurotrophic factor gene (BDNF) polymorphisms and brain morphology in patients with schizophrenia and healthy control subjects. Four BDNF polymorphisms were genotyped and analyzed versus 39 brain volume measures in 96 patients with schizophrenia or schizoaffective disorder and 104 healthy subjects. In all subjects, quantitative data on segmented gray, white, and cerebrospinal fluid (CSF) tissue class volumes of total brain and major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 69 publications
3
54
1
1
Order By: Relevance
“…Out of 126 studies initially found by the systematic search, 14 studies measured hippocampal volumes in healthy subjects genotyped for BDNF gene Val66Met polymorphism (Szeszko et al 2005;Agartz et al 2006;Bueller et al 2006;Frodl et al 2007;Takahashi et al 2008b;Chepenik et al 2009;Dutt et al 2009;Jessen et al 2009;Joffe et al 2009;Koolschijn et al 2010;Benjamin et al 2010;Gonul et al 2011;Haukvik et al 2010;Karnik et al 2010). The study by (Haukvik et al 2010) overlapped with the (Agartz et al 2006) study, thus yielding 13 non-overlaping datasets.…”
Section: Results Of the Systematic Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of 126 studies initially found by the systematic search, 14 studies measured hippocampal volumes in healthy subjects genotyped for BDNF gene Val66Met polymorphism (Szeszko et al 2005;Agartz et al 2006;Bueller et al 2006;Frodl et al 2007;Takahashi et al 2008b;Chepenik et al 2009;Dutt et al 2009;Jessen et al 2009;Joffe et al 2009;Koolschijn et al 2010;Benjamin et al 2010;Gonul et al 2011;Haukvik et al 2010;Karnik et al 2010). The study by (Haukvik et al 2010) overlapped with the (Agartz et al 2006) study, thus yielding 13 non-overlaping datasets.…”
Section: Results Of the Systematic Searchmentioning
confidence: 99%
“…The study by (Haukvik et al 2010) overlapped with the (Agartz et al 2006) study, thus yielding 13 non-overlaping datasets. The studies by Joffe et al (2009) and Karnik et al (2010) did not use manual tracing, but rather automated segmentation and registration based procedures for hippocampal volumetry, thus failing inclusion criterion 3.…”
Section: Results Of the Systematic Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudos de imagem sugerem que a variações dos polimorfismos do gene BDNF podem ter diferentes conseqüências na morfologia cerebral e podem ser diferentes entre indivíduos saudáveis e com esquizofrenia (Agartz I et al, 2006).…”
Section: A Val66met E Esquizofreniaunclassified